Competitive Strategy Analysis in The Society 5.0 Era Using the Meta-SWOT Approach - Widodo, Fadhillah Rayhan; Rofiaty (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to identify and analyze appropriate competitive strategies for Tugu Malang, an online media company based in Malang City, to maintain relevance and strengthen its market position amid increasing digital media competition and technological changes. Design/Methodology/Approach – This study employs the Meta-SWOT approach by integrating the Resource-Based View (RBV) framework to analyze internal resources and capabilities, and the PESTEL framework to evaluate external environmental factors. Data were collected through questionnaires, document reviews, and interviews with nine informants, including company management and deputy editors-in-chief from three competing companies. The findings were further analyzed using the Grand Strategy Matrix to determine the company’s strategic position. Findings – The results indicate that Tugu Malang has twelve valuable resources and capabilities that are rare, difficult to imitate, and well-organized, including funding sources, organizational culture, workforce skills, customer satisfaction, technology investment, human resource development, quality control, legal compliance, employee retention, marketing media, pricing, and product variety. The PESTEL analysis identifies external opportunities and threats related to government support, political conditions, technological innovation, community engagement, economic instability, and regulatory changes. Based on the Grand Strategy Matrix, Tugu Malang is positioned in Quadrant I, indicating a strong strategic position. The recommended strategies include market penetration, market development, and product development. Originality/Value This research provides value by integrating the Meta-SWOT approach with RBV and PESTEL analyses to generate strategic insights specifically for online media in the Society 5.0 era, offering a structured framework that can guide similar digital media companies in navigating dynamic environmental challenges.